The Process of Creating the Script for the Performance of, "Bermulanya Di Sini…Kedah Tua" - Mumtaz Begum Aboo Backer; Halimi Mohd Noh; Husaini Yaacob (Wacana Seni Journal of Arts Discourse, 2019)
Bermulanya Di Sini…Kedah Tua" is an artistic theatrical production, the outcome of a collaborative effort between performers and archeologists at the Lembah Bujang, Kedah. The creation of the script for the production goes with the same title of "Bermulanya Di Sini…Kedah Tua" is inspired by historical narratives and literary sources derived from the ancient civilisation at Lembah Bujang also known as Kedah Tua. "Bermulanya Di Sini…Kedah Tua" translated as Kedah Tua...where it all began, marks the beginning of a new historical discovery, especially at Sungai Batu, an area in Lembah Bujang to be recognised as the oldest ancient civilisation in Southeast Asia. The key steps involved in creating the script for the theatrical production were (1) translating archaeological artefacts and architectural remains at Kedah Tua and (2) interpreting existing literary works, historical narratives, and artists impression about Kedah Tua. The methodology applied in creating the script is a combination of practice led research and textual analysis methods; a systematic method for describing, interpreting, analysing, and evaluating performative interpretations of the available field texts which provided a framework for a re-imagined scenario and also the artistic license to stretch the boundaries of the historical discourse. This method allowed the script to picture the setting of Kedah Tua between 2nd CE and 6th CE, which further establishes a premise upon the varying performance elements such as the plot, diction, and characterisation.